Advanced engineering and technology selected, peer reviewed papers from the International Conference on Advanced Engineering and Technology (ICAET 2014), December 19-21, 2014, Incheon, South Korea (Applied Mechanics and Materials, 2015)
Collection of selected, peer reviewed papers from the International Conference on Advanced Engineering and Technology (ICAET 2014), December 19-21, 2014, Incheon, South Korea. The 260 papers are grouped as follows: Chapter 1: Metal and Alloy Materials and Technologies; Chapter 2: Advanced Materials Engineering, Technologies and Applications; Chapter 3: Material Testing, Analysis and Processing Technology; Chapter 4: Structural Engineering, Dynamics and Applied Mechanics, Building Materials and Building Management; Chapter 5: Mechanical Engineering and Design, Manufacturing Technologies; Chapte 6: Automation, Robotics and Control; Chapter 7: Measurement, Monitoring and Detection, Identification and Advanced Systems; Chapter 8: Communication, Graphic and Image Processing, Information Technologies Applications; Chapter 9: Energy Control and Power Systems, Electrical and Electronic Engineering; Chapter 10: Disaster Prevention and Mitigation Technology, Environmental Protection and Safety Management; Chapter 11: Industrial Engineering, Production Quality and Management